2011
DOI: 10.7882/az.2011.010
|View full text |Cite
|
Sign up to set email alerts
|

Public perceptions of foxes and fox eradication in Tasmania

Abstract: The red fox Vulpes vulpes is one of the most destructive invasive species in mainland Australia and has recently been introduced to Tasmania. This paper reports the results of a survey conducted in Tasmania in mid-2006, to ascertain the public's views about foxes, their presence in Tasmania and what, if anything, should be done about them if, in fact, they are present. The survey found that public opinion among Tasmanians surveyed was overwhelmingly and vehemently opposed to the presence of foxes and indicated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…We don't want history to repeat. So there's been a vigorous (if mainly vocal) response to a new wave of mammal loss in northern Australia (Woinarski et al 2011), and rapid concern and action taken on the recent appearance of red foxes Vulpes vulpes in Tasmania (Fisher et al 2011). We argue that it is the loss of the thylacine, and the 18 other Australia mammals now extinct, that prompts this action.…”
Section: Australian Zoologist Volume 38 (3)mentioning
confidence: 88%
“…We don't want history to repeat. So there's been a vigorous (if mainly vocal) response to a new wave of mammal loss in northern Australia (Woinarski et al 2011), and rapid concern and action taken on the recent appearance of red foxes Vulpes vulpes in Tasmania (Fisher et al 2011). We argue that it is the loss of the thylacine, and the 18 other Australia mammals now extinct, that prompts this action.…”
Section: Australian Zoologist Volume 38 (3)mentioning
confidence: 88%
“…Similar surveys assessing stakeholder acceptability of toxicant use in invasive species management had comparable findings. Specifically, Fisher et al [ 69 ] found that approximately 59%, 35%, and 28% of survey respondents were supportive of the use of cyanide baiting, 1080 baiting, and humane toxins in fox eradication efforts on Tasmania, respectively. Comparatively, Farnworth et al [ 70 ] found overwhelming acceptance of toxicant use in the control of non-native species to New Zealand by the general public and conservation groups.…”
Section: Discussionmentioning
confidence: 99%
“…The red fox is one of the most damaging invasive predators in Australia, having been pivotal to half of the known mammal extinctions worldwide in the last 200 years (Kinnear et al 2002;Short and Smith 1994). This case provided us with the opportunity to examine a number of the socio-political constraints to eradication and control described above, namely, the island is inhabited; eradication methods are seen by some community members as inhumane (Fisher et al 2011); and half of surveyed community stakeholders doubt that foxes are present (Correy and Correy 2012), and this doubt is hampering eradication efforts (Blackman et al 2013).…”
Section: Fox Eradication In Tasmania Australiamentioning
confidence: 99%